Emphysema Then and Now - William M Thurlbeck (Canadian Respiratory Journal)
The present definition or emphysema has three components: enlargement of airspaces. destruction or their walls and lack of fibrosis. Enlargement can be recognized by measuring the intcralvcolar wall distance or by comparing the airspaces under cnnsiJcration with adjacent or distant normal lung. Most recently. destruction has been defined as disappearance or disturbance or the orderly appearance or the pulmonary acinus (gas exchanging tissue). Other authors have also suggested that destruction can be recognized by abnonnal holes (fenestrae) in airspace walls or by the 'destructive index '. fibrosis appears to be an integral part of centrilobular. distal acinar and irregular airspace enlargement. The presence of fibrosis should not preclude emphysema by definition. Emphysema should be recognized by practicable methods and should be measured in some way. Evidence is presented that abnormal elastic properties of the lung are not due to emphysema but reside in the surrounding lung; the altered elastic properties may be due to alterations in the glycoprotein matrix of the lung. Altered elastic properties arc a relatively poor predictor of emphysema as gellerally defined and recognized. Computed tomography can recognize emphysema quite well, but appears to underestimate it and is not accurate in lungs with mild or no emphysema. Emphysema can be best diagnosed in life with an in tegrated approach using clinical data. radiological evidence of lung enlargement and the single breath diffusing capacity (transfer factor) for carbon monoxide. While knowledge of emphysema has dramatically increased in the past 30 years. much more remains to be done. and this requires new and more thorough approaches.